Effect of tegoprazan, a novel potassium-competitive acid blocker, on non-steroidal anti-inflammatory drug (NSAID)-induced enteropathy - Hyun Jung Lee; Ji Wook Moon; Seong-Joon Koh; Jong Pil Im; Byeong Gwan Kim; Joo Sung Kim (Scientific Reports)
Abstract As the non-steroidal anti-inflammatory drugs (NSAIDs) are typically used in the treatment of chronic conditions, the incidence of NSAID-induced enteropathy is increasing. Given the challenges associated with discontinuing NSAIDs, effective preventive and treatment strategies are crucial. We assessed the effect of tegoprazan on NSAID-induced enteropathy. Human epithelial cells (HIEC-6, HT-29, and Caco-2) were treated with indomethacin and tegoprazan. Cell viability, expression levels of tight-junction proteins, levels of proinflammatory cytokines, and apoptosis were assessed by conducting MTT assays, RT-PCR, western blotting, and immunofluorescence staining, respectively. Tegoprazan significantly ameliorated the inhibition of cell proliferation induced by indomethacin. Tegoprazan also mitigated the suppression of occludin and ZO-1 expression by indomethacin, thereby restoring intestinal permeability. Additionally, tegoprazan reversed the indomethacin-induced elevation of the levels of proinflammatory cytokines and the rate of apoptosis of small intestinal epithelial cells. Our findings indicate that tegoprazan exerts a protective effect against NSAID-induced injury to small intestinal epithelial cells. The effect involves enhancement of the expression levels of tight junction proteins and the suppression of inflammation and apoptosis.